Diastereoselectivities in Reductions of α-Alkoxy Ketones Are Not Always Correlated to Chelation-Induced Rate Acceleration - Bartolo, Nicole D.; Hornstein, Alana L.; Zhao, Annie Y.; Woerpel, K. A. (Synthesis, 2019)
The chelation-control model is used to predict stereochemical outcomes of many organometallic reactions. Diastereoselectivity arises due to reaction with a chelated intermediate with sterically differentiated faces. Earlier studies with dimethylmagnesium established that the chelated intermediate is a minor component of the reaction mixture, so reaction with the chelated intermediate must be faster than reaction with a non-chelated intermediate. High diastereoselectivity and chelation-induced rate acceleration are correlated with some hydride reducing agents. There are examples in which diastereoselectivity is high, but chelation-induced rate acceleration is not observed, however. In other cases, chelation-induced rate acceleration is observed, but diastereoselectivity remains low. These experiments illustrate that a revision to the chelation-control model is needed.
Keywords: hydride reductions; chelation control; stereoselectivity